Beaver in tidal habitat: Examples from the Pacific Northwest - W. Gregory Hood (PLoS ONE, 2026)
Beaver are typically considered fluvial or lacustrine animals, often converting lotic habitats into lentic ones with their dams. This results in extensive changes in ecosystem structure and processes so that beaver are considered the quintessential ecosystem engineer. Here I broaden our appreciation of the adaptability of beaver by describing their widespread presence in tidal river deltas and estuaries of the Pacific Northwest (coastal British Columbia, Washington, and Oregon), where tides can range between 1.5 and 5.0 m. These observations expand the known habitat distribution of beaver and invite investigation of the ecosystem consequences of beaver in tidal wetlands. In these oligohaline to fresh tidal systems, channel profile surveys with real-time kinematic (RTK)-GPS show that beaver dams are typically flooded on higher high tides, only impounding water at low tide to allow beaver movement during this time. Tidal beaver dam density per km was more than twice that reported in the fluvial literature, while mean dam head was about 80% and mean dam height about 60% of fluvial dams. Low-tide beaver pool depths were 75% of fluvial beaver ponds, while pool areas were 67% of their fluvial counterparts. The comparable beaver dam metrics between fluvial and tidal systems suggests their role in tidal ecosystems may be comparably significant. Inspection of Google Earth aerial photographs back to 1990 indicated that tidal beaver dams can persist for at least 35 years, spanning several generations of beaver. Given the ecosystem importance of beaver in fluvial and lacustrine habitats, better understanding of the distribution and ecosystem role of beaver in tidal wetland habitat, and the geometry of their dams and low-tide pools, would likely allow more effective restoration of estuarine habitat that is critical to a variety of fish and wildlife, including threatened species such as Chinook and coho salmon.